Experiences and treatment patterns of hypogonadal men in a U.S. health system. Issue 10 (28th March 2014) - Shortridge, E. F.; Polzer, P.; Donga, P.; Blanchette, C. M.; Fang, Y.; Burudpakdee, C.; Carswell, B.
Summary Objective To examine self‐reported experiences with hypogonadism (HG) and patterns of testosterone replacement therapy (TRT) in men seeking care in a U.S. healthcare system. Methods Men ≥ 18 years old with HG were identified from the 2008–2010 Reliant electronic medical records database. Surveys, including validated instruments for measuring symptoms of HG, were collected and evaluated for demographic and behavioural data. Results Surveys were mailed to 133 men with HG in 2012. Of the 107 surveys returned, 95 were included in the final analysis. Most respondents were Caucasian (90.5%). Men reported developing symptoms of HG, as well as being diagnosed, at a median age of 50 years. The most common symptoms reported as reasons for seeking treatment were erectile dysfunction (66.3%), fatigue (59.0%) and decreased sex drive (57.9%). These continued to be the most bothersome symptoms at the time of the survey regardless of whether the patient received treatment, although men who were currently taking TRT reported less severe symptoms. Approximately 88% of men reported taking TRT at some point, with 61.9% on therapy at the time of the survey. Conclusions This study examined men's experiences with HG, including symptoms, quality of life, and treatments. Some symptoms continued despite treatment, and therapy was discontinued at a high rate, which men generally attributed to cost and perceptions of efficacy. In light of this lack of adherence, patients may benefit from appropriate expectation setting regarding reasonable timelines for symptom improvement, the strengths and challenges of various TRT formulations, the importance of adherence and the benefits and risks of TRT.